Organic matter properties and their relation to phosphorus and nitrogen concentrations in Swedish agricultural streams - Ehnvall, Betty (2017)
Many agricultural streams in Sweden exhibit high concentrations of nitrogen, phosphorus, suspended sediments and dissolved organic matter (DOM). Together these substances cause eutrophication in streams, rivers and eventually the Baltic Sea. The interactions between different fractions of DOM and nutrients are not very well understood. The aims of this study were to investigate spatial and temporal patterns in DOM in Swedish agricultural streams and to understand how DOM and nutrients interact. Ten catchments in south – central Sweden that are dominated by arable land were compared. Most of the catchments have intensive crop production with high nutrient turnover and in some the livestock density is also high. All these factors can affect the qualitative and quantitative properties of DOM. Water samples from the catchments and fields were analyzed for week 2, 4, 6 and 8 2017, covering a time period of one and a half month. DOM was analyzed optically using excitation-emission fluorescence spectroscopy (EEM) and absorbance spectroscopy (UV/Vis). A number of spectroscopic indices were used to describe the DOM properties. Turbidity, total organic carbon, dissolved organic carbon, pH and orthophosphate concentration were also analyzed. In addition, information about nitrogen and phosphorus concentrations was available. Only weak temporal trends could be found in the dataset but clear spatial differences in DOM properties were observed between the catchments. Catchment F26 differed from most other catchments by having heavier, more labile and to a greater extent plant derived DOM. Catchments O18 and E21 had opposite characteristics to F26 in nearly all studied indices. The DOM was fresher and the molecular weight lower. Correlations between phosphorus and several particulate properties could be found, which describe the absorbing nature of dissolved phosphorus. Nitrogen correlated with the molecular weight of DOM and with the ratio of humic-like to fuvic-like fluorophores. Neither nitrogen nor phosphorus correlated with the protein-like fluorophore. The results demonstrate the importance of reducing leaching of particles and large dissolved organic molecules to streams, since these fractions are related to nitrogen and phosphorus concentrations. This can be done by installing ponds and wetlands and by preventing erosion along stream banks. However, catchment specific actions need to be taken, since the study clearly demonstrated differences between catchments when it comes to DOM and nutrient properties.